การนำเสนอแนวทางการพัฒนาความสามารถทางการสอนศิลปศึกษาสำหรับครูประจำการ PROPOSED GUIDELINES TO DEVELOP ART EDUCATION TEACHING ABILITY OF IN-SERVICE - ญาติสมบูรณ์ พิภัช; พลประเสริฐ อภิชาติ (An Online Journal of Education, 2018)
Abstract This objectives of this research were to 1) Study the effect of demand and development of teaching art education 2) Proposed guidelines for the development of teaching art education for in-service art teachers. It is a constituent survey the in-service art teachers under Obec 379 people and development specialist arts teacher 34 people. The findings revealed that The expected result of the development of the art of teaching. Art teachers expect to get more knowledge and artistic skills. The social conduct to be used in teaching, such as the choice of how to teach art. The laboratory Media production, including drilling appraisal artistic creation. Efficiency of Development Activities associated with the teaching workload. Both theory and artistic skills along the way. Including new teaching techniques. Monitoring by the authorities and colleagues. Speakers are artists, professionals and teaching art theory and practice. The place is a museum, art gallery, which during the first weeks of the semester. It is the right moment at the statistical level of significance. 05. Guidelines for Development The preparation Explore the art of the teacher to easily determine the content. Activities and to convey both theoretical and artistic skills along the way. The judge intervened in art. The works of art, media to media. The Gallery,Meeting place The action of art activities to assess the knowledge base of teachers. The lecture with demonstration and the opportunity to practice with the teacher guiding each step. The event focused on its use in teaching. The duration and follow-up. The time required to develop the first weeks of the semester. In order for teachers to practice the art fully. Evaluation forms practicing critics of Friends of the activity. Using the knowledge gained and guided by trainers. After he developed Teacher, colleague, and speakers included follow-up period. In the form of reflections and measurement of achievement in the classroom.